Caracterização química e avaliação da atividade e do mecanismo de ação anti-inflamatório do extrato hidroetanólico da entrecasca do caule de Virola elongata (Benth.) Warb. - Di Serio, Bruna Fioravante (2023)
Virola elongata is a leafy tree that occurs in the phytogeographic domain of the Amazon, mainly known in Brazil as bicuíba or mucuíba. Its bark and stem are popularly used in the form of infusion and aqueous macerate or in cachaça or white wine to treat inflammation and other conditions. However, there are still no reports proving its use as an anti-inflammatory. Therefore, this work aimed to evaluate the anti-inflammatory activity and possible mechanisms of action of the hydroethanolic extract of the inner bark of the stem of V. elongata (HEVe). The anti-inflammatory activity and mechanisms of action of HEVe (5, 25 and 100 mg/kg p.o.) were evaluated by lipopolysaccharide-induced peritonitis in female mice, to determinate, in the peritoneal lavage (PL), the number of total leukocytes and the differential count, as well as the levels of pro- (TNF-α and IL1β) and anti-inflammatory (IL-10) cytokines. The HEVe was prepared by macerating the inner bark of the stem in a 70% hydroethanolic solution (1:3 w/v). Phytochemical analysis of HEVe was carried out using ultra high performance liquid chromatography (UPLC), mass spectrometry and electrospray ionization. The local anti-inflammatory activity of HEVe gel (1, 3 and 9%) was analyzed in the model of topical dermatitis induced by croton oil. RAW 264.7 cells stimulated by LPS (1µg/mL) were used to verify the direct effect of HEVe on the production of cytokines (TNF-α, IL-1β and IL-13) and nitric oxide (NO). Analysis of the phytochemical profile of HEVe by ultrahigh performance liquid chromatography (UPLC), mass spectrometry and electrospray ionization indicated the presence of phenolic acids, neolignans, flavonoids and monomeric catechins. In acute peritonitis, HEVe (5, 25 and 100 mg/kg) reduced (p < 0.001) the number of total leukocytes (69.2, 81.6 and 76.3%) and neutrophils (94.8, 98 .0 and 93.0%) in relation to the vehicle group. HEVe at a dose of 5 mg/kg reduced the concentration of TNF-α in the PL by 39.6% (p < 0.001), while at doses of 25 and 100 mg/kg the reduction was 18.6 and 25.5% (p < 0.01), respectively. IL-1β levels were reduced (22.1%, p < 0.05) by HEVe only with the 25 mg/kg dose. Topical dermatitis was reduced (p < 0.001) by 43.0, 30.4 and 29.5% by local application of HEVe gel (1, 3 and 9%). Treatment of RAW 264.7 cells with HEVe (6.25 – 400 µg/mL) did not cause cytotoxicity, with IC50 = 302.58 ± 5.82 μg/mL in 24 h. Pre-treatment of LPS-stimulated RAW 264.7 with HEVe (1, 5 and 20 µg/mL) reduced TNF-α concentrations in 5.3, 6.3 and 7.0% (p < 0.05) and IL-1β in 42.0, 49.7 and 48.3% (p < 0.01) and increased (p < 0.001) IL-13 levels in 27.7 and 32.9%, in the concentrations of 5 and 20 µg/ml, respectively. NO levels were reduced (p < 0.001) in 54.8, 71.0 and 65.3%. These results support the popular use of alcoholic preparations from the stem bark of V. elongata for inflammation. The local and systemic anti-inflammatory action of HEVe is multi-target, due at least to the leukocyte recruitment reduction, the direct modulation of cytokine release, as well as the reduction in NO levels. This activity of HEVe may be due to the combined action of secondary metabolites from the classes of phenolic acids, stilbenes, neolignans and flavonoids, making HEVe a potential antiinflammatory herbal medicine, with very low cytotoxicity.